How an In-Store Self-Service Technology Impacts Customer Shopping Experience, Satisfaction and WOM Intentions - Gagné, Virginie; Tep, Sandrine Prom; Arcand, Manon; St-Onge, Anik; N’Guessan, Emmanuel (Journal of Marketing Development and Competitiveness, 2024)
Retailers are increasingly using self-service technologies (SSTs) in-store. However, their impacts are not well known. The objective of this study is to establish whether the use of SST and its key characteristics (perceived ease of use (PEOU) and perceived usefulness (PU)) has a significant effect on the customer experience (i.e., cognitive, affective, sensory, behavioral and social dimensions). The effect of these dimensions on satisfaction and positive word-of-mouth (WOM) intent were also investigated. We conducted an in-store experiment in which half of the 102 participants chose sports shoes using an interactive wall while a salesperson exclusively assisted the other half. The results demonstrate that the cognitive/positive affective and sensory dimensions of the experience are positively influenced by use of SST while the social dimension is diminished. Further, when SST was used, the negative affect increased. For customers who used the SST, PEOU and PU contribute to enhance all dimensions of the experience, except for PEOU which lowers the social experience. Customer experience positively impact consumer’s satisfaction and WOM intent.